2011
DOI: 10.1111/j.1530-0277.2011.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Rat Cerebellar Golgi Cells by Ethanol: Further Characterization of the Mechanism

Abstract: Background Studies with rodents suggest that acute ethanol exposure impairs information flow through the cerebellar cortex, in part, by increasing GABAergic input to granule cells. Experiments suggest that an increase in the excitability of specialized GABAergic interneurons that regulate granule cell activity (i.e. Golgi cells, GoCs) contributes to this effect. In GoCs, ethanol increases spontaneous action potential firing frequency, decreased the afterhyperpolarization amplitude, and depolarized the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 62 publications
(111 reference statements)
6
22
0
1
Order By: Relevance
“…Instead, when EtOH does affect NHP GC GABA A R transmission it is via excitation of Golgi cells and consequent increased vesicular release of GABA, similar to what has been reported for SDRs (Carta et al, 2004; Botta et al, 2007a,b, 2010, 2012). …”
Section: Discussionsupporting
confidence: 72%
“…Instead, when EtOH does affect NHP GC GABA A R transmission it is via excitation of Golgi cells and consequent increased vesicular release of GABA, similar to what has been reported for SDRs (Carta et al, 2004; Botta et al, 2007a,b, 2010, 2012). …”
Section: Discussionsupporting
confidence: 72%
“…Extrasynaptic GABA levels are also reduced, thereby decreasing CGN-I tonic . (C) Acute EtOH inhibits the Na + /K + -ATPase found on GoCs (and possibly also a quinidine-sensitive K + -channel [20]). Inhibition of these membrane proteins depolarizes the membrane potential of GoCs, thereby increasing spontaneous GoC firing and phasic GABA release onto CGNs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, acute EtOH exposure increases both the frequency of sIPSCs driven by GoC firing and the magnitude of CGN-I tonic , and these effects are blocked by TTX [18]. Recordings from GoCs revealed that EtOH dose-dependently increases spontaneous GoC firing, an effect that appears to be, at least in part, a consequence of slight inhibition of the Na + /K + -ATPase [18], [19], [20]. In vivo electrophysiological studies indicate that acute EtOH exposure both increases spontaneous GoC firing and inhibits sensory responses of CGNs [21], [22].…”
Section: Introductionmentioning
confidence: 95%
“…Tonic inhibition is mediated by extrasynaptic GABA A Rs that are activated by ambient levels of GABA whose source remains controversial (Brickley and Mody, 2012; Diaz et al, 2011; Lee et al, 2010). While GABAergic transmission at CGNs has been shown to be an important target for acute EtOH in the mature cerebellar cortex (Botta et al, 2010; Botta et al, 2007; Botta et al, 2011; Carta et al, 2004; Hanchar et al, 2005), the impact of EtOH exposure during development has not been explored. Importantly, the development of GABAergic transmission in other brain regions has been shown to be impaired in various models of 3 rd trimester-equivalent EtOH exposure (Everett et al, 2012; Hsiao et al, 1998; Zucca and Valenzuela, 2010).…”
Section: Introductionmentioning
confidence: 99%